Toward the Realization of Policy-Oriented Enterprise Management. - Kaiser, Matthias (Computer (00189162), 2007)
The article discusses strategies and technologies for adapting business processes to business goals. Enterprise software systems tend to be monolithic and inflexible. Service-oriented architecture (SOA) offers some improvement but introduces issues of its own. The author presents an "enterprise physics" metaphor whereby business objects and policies are analogous to physical objects and physical laws, respectively. Enterprise physics allows for quick process development, consistent process design, and flexibility to deal with ad hoc business objectives.